Horrible British Histories: Young people in museums interrogating national identity through principles and practices of critical pedagogy - Sadia Habib (PRISM)
This paper explores the importance of supporting young people in exploring identities and belongings in the cultural heritage sector. When working with young people in British museums, creating open and safe spaces for discussing the entanglements of contemporary multicultural identities with the legacies of British colonialism is necessary and long overdue.  By employing the principles and practices of critical pedagogy, heritage organisations can interrogate the dominant narratives about identity and belonging in Britain, and work with young people to highlight shifting, fluid and multiple identities and belongings in contemporary Britain.